2020
DOI: 10.1212/nxg.0000000000000415
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic outcomes in Friedreich ataxia

Abstract: ObjectiveTo investigate the pattern of progression of neurologic impairment in Friedreich ataxia (FRDA) and identify patients with fast disease progression as detected by clinical rating scales.MethodsClinical, demographic, and genetic data were analyzed from 54 patients with FRDA included at the Brussels site of the European Friedreich's Ataxia Consortium for Translational Studies, with an average prospective follow-up of 4 years.ResultsAfferent ataxia predated other features of FRDA, followed by cerebellar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 26 publications
7
36
0
Order By: Relevance
“…This abnormality was more severe in those with higher SARA scores and disease duration. Progressive pyramidal tracts involvement in FRDA is supported by neuropathological, clinical, and electrophysiological findings 32,33 Weakness, spasticity, and muscle atrophy of the hands are eventually found in over two‐third of cases 34 . Accordingly, we found that FT rate slowing was more severe in patients with higher global SARA scores, reflecting more advanced disease.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This abnormality was more severe in those with higher SARA scores and disease duration. Progressive pyramidal tracts involvement in FRDA is supported by neuropathological, clinical, and electrophysiological findings 32,33 Weakness, spasticity, and muscle atrophy of the hands are eventually found in over two‐third of cases 34 . Accordingly, we found that FT rate slowing was more severe in patients with higher global SARA scores, reflecting more advanced disease.…”
Section: Discussionmentioning
confidence: 51%
“…Progressive pyramidal tracts involvement in FRDA is supported by neuropathological, clinical, and electrophysiological findings 32,33 Weakness, spasticity, and muscle atrophy of the hands are eventually found in over two-third of cases. 34 Accordingly, we found that FT rate slowing was more severe in patients with higher global SARA scores, reflecting more advanced disease. FRDA patients with longer disease duration also showed more severe pyramidal tract dysfunction as assessed by MEPs, with more marked increase of CMCT.…”
Section: Discussionmentioning
confidence: 64%
“…Clinically, the pattern of progression of neurological impairment in FRDA shows that the perceived onset of neurological symptoms corresponds to the appearance of cerebellar ataxia, affecting gait before stance, speech, and limb coordination. [22][23][24] Even though proprioceptive ataxia usually precedes the appearance of cerebellar symptoms, as shown by a Romberg sign in almost all patients at the time of diagnosis, 25 it is usually mild and effectively compensated by visual control. Gait and stance worsen until patients lose the ability to walk.…”
Section: Cerebellar Systemmentioning
confidence: 99%
“…However, some degree of upper limb dysmetria is almost always present in recently diagnosed patients, as shown by clinical rating scales and functional tests. 22,[24][25][26] Dysarthria may be initially absent, but most patients become dysarthric within a few years after diagnosis. 22,23,27 Upper limb dysmetria, dysarthria, and eventually dysphagia continue to worsen in all patients, contributing to increasing disability in the late stages of the disease.…”
Section: Cerebellar Systemmentioning
confidence: 99%
“…In addition, the influence of epigenetic and environmental factors in the progression of the pathology further impact on the capability to define the natural histories of patients. The development and consensus of new scales such as SARA [204] and mFARS [39], together with the generation of patient records containing comprehensive clinic and epidemiologic information is essential but results are still limited and dispersed. All these aspects hinder the proper classification of patients for the design and analysis of clinical tests.…”
Section: Discussionmentioning
confidence: 99%